Exponentially weighted moving average charts to compare observed and expected values for monitoring risk-adjusted hospital indicators. Issue 6 (5th January 2011) - Cook, D A; Coory, M; Webster, R A
Abstract : Objective: To introduce a new type of risk-adjusted (RA) exponentially weighted moving average (EWMA) chart and to compare it to a commonly used type of variable life adjusted display chart for analysis of patient outcomes. Data: Routine inpatient data on mortality following admission for acute myocardial infarction, from all public and private hospitals in Queensland, Australia. Methods: The RA-EWMA plots the EWMA of the observed and predicted values. Predicted values were obtained from a logistic regression model for all hospitals in Queensland. The EWMA of the predicted values is a moving centre line, reflecting current patient case mix at a particular hospital. Thresholds around this moving centre line provide a scale by which to assess the importance of trends in the EWMA of the observed values. Results: The RA-EWMA chart can be designed to have equivalent performance, in terms of average run lengths, as variable life adjusted display chart. The advantages of the RA-EWMA are that it communicates information about the current level of an indicator in a direct and understandable way, and it explicitly displays information about the current patient case mix. Also, because it is not reset, the RA-EWMA is a more natural chart to use in health, where it is exceedingly rare to stop or dramatically and abruptly alter a process of care. Conclusion: The RA-EWMA chart is a direct and intuitive way to display information about an indicator while accounting for differences in case mix.